Analysis of Occupational Posture Risk and Physiological Load in Grinding and Moving HVAC Filter Products Using Rula-Reba, Heart Rate, and Borg RPE - Soenandi, Iwan Aang; Sabattian, Roy Theo (Jurnal Improsci, 2026)
This study aims to study the risk of work posture, heart rate response, and operator workload perception in gluing, lifting, and laying HVAC filter products in the epoxy center area of PT XY. In this study, the Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA), Heart Rate, and Borg Rating of Perceived Exertion (Borg RPE) methods were used. This study was conducted on six operators through field observation, photo/video documentation, Heart Rate measurement, Borg RPE assessment, manual handling recording, anthropometric measurements, and brief interviews. The results showed that, compared to gluing and lifting activities, laying activities had the most prominent ergonomic risk patterns. This is shown by relatively high RULA and REBA scores, the highest average heart rate, and the perception of workload which is generally in the weight category. In addition, gluing activities indicate postural risks, especially due to the posture of bending, reaching, and the use of nozzles and hoses during the work process. Because it involves moving products manually, lifting jobs have a relatively lower risk. However, this work still requires supervision. The mapping results show that improvement should be a top priority. Then followed by gluing and product lifting activities. Ergonomic improvements are aimed at adjusting the placement height of the pallet support facility, regulating the position of products, hoses, and nozzles during immersion, and reducing manual displacement distances when lifting. The results of the simulation of the reassessment of RULA and REBA based on the proposed posture showed the possibility of reducing the risk of working posture, especially in the excavation and laying work.